(untitled) (Marketing Journal, 2025)
This article explores the specific characteristics of leasing services in the Republic of Uzbekistan. It presents theoretical perspectives on leasing, outlines methods for calculating lease payments, and offers recommendations for improving the process of providing leasing services.